2006
DOI: 10.1007/s11837-006-0182-x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of phase transformation behavior in sputter-deposited PtMn thin films

Abstract: Sputter-deposited, equiatomic PtMn thin fi lms have application in giant magnetoresistive spin valves, tunneling magnetoresistive spin valves, and magnetic random access memory. However, the as-deposited fi lms are found to be a disordered A1 phase in a paramagnetic state rather than an antiferromagnetic phase with L1 0 structure, which is needed for device operation. Therefore, a postannealing step is required to induce the phase transformation from the asdeposited A1 face-centered-cubic phase to the antiferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…1(c)) show very good uniformity with Mn : Pt ratio of 76 : 24 which results in a composition of Mn 3.04 Pt 0.96 . This slight deviation in stoichiometry with excess Mn concentration is not expected to destabilize the structure of Mn 3 Pt, as reported in the study of hexagonal Mn 3 Sn thin films [21,32]. Structural characterization of the films using X-ray diffraction (Rigaku diffractometer using Cobalt K α source, λ = 1.7903 Å), performed in ω − 2θ geometry, show dominant (100) with weaker (200) peak and a (111) peak (see fig.…”
Section: Thin Film Preparation and Structural Characterizationsupporting
confidence: 60%
See 1 more Smart Citation
“…1(c)) show very good uniformity with Mn : Pt ratio of 76 : 24 which results in a composition of Mn 3.04 Pt 0.96 . This slight deviation in stoichiometry with excess Mn concentration is not expected to destabilize the structure of Mn 3 Pt, as reported in the study of hexagonal Mn 3 Sn thin films [21,32]. Structural characterization of the films using X-ray diffraction (Rigaku diffractometer using Cobalt K α source, λ = 1.7903 Å), performed in ω − 2θ geometry, show dominant (100) with weaker (200) peak and a (111) peak (see fig.…”
Section: Thin Film Preparation and Structural Characterizationsupporting
confidence: 60%
“…1(a) and (b)) [18,19]. Experimentally, Mn 3 X compounds are observed to undergo temperature driven phase transitions between collinear AFM, non-collinear AFM and/or canted ferromagnetism state depending on the composition, microstructure and growth procedure [20,21]. In the collinear AFM state, the Berry curvature becomes zero due to the symmetry [22], while in the non-collinear phase, this special spin arrangement of Mn moments support finite Berry curvature [2] leading to the observation of anomalous Hall conductivity (AHC).…”
Section: Introductionmentioning
confidence: 99%
“…1(b) for comparison with a small arrow on the vertical axis. 2,30) Nevertheless, to prove the transformation from the FCC phase to the FCT phase for PtMn, we performed an in-plane XRD that is shown in Fig. 3.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Exchange bias (EB) can be observed by the exchange coupling between the magnetic moments of an antiferromagnet (AFM) and those of a ferromagnet (FM) at an AFM/ FM interface. 1,2) Extensive studies on using exchange biasing materials as pinned layers of a spin valve structures in giantmagnetoresistive (GMR) devices 3) and magnetic tunnel junctions 4,5) have been conducted because of their applications, such as in read heads in hard disk drives and magnetic random access memory cells. Nowadays, MTJs are also used for bio-magnetic field sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The derivative heat flow diagrams from 700-1200 °C showed that the heat flow in the presence of the additive was divided into two separate peaks. The first peak was related to an expected phase transformation from the Pt-Mn phase diagram [32] or Mn oxide phase modifications. The second peak might be attributed to the alloy melting or unknown phase transformation.…”
Section: Materials Characterizationmentioning
confidence: 99%